Larval therapy from the patient’s perspective - da Silva, Simone Maria; Medeiros Millions, Rejane; Almeida , Rita de Cássia; da Costa , João Evangelista (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: to describe the perception of the patient undergoing larval therapy. Method: qualitative, exploratory-descriptive study, using oral history as a data collection technique and methodological framework, in the form of oral life history. Six patients with difficult-to-heal wounds participated in the study, followed by the dressing committee of a teaching hospital in Natal, Rio Grande do Norte, undergoing larval therapy. Results: the testimonies of the patients/collaborators point to various values, such as belief, fear, acceptance, improvement of the wound and pain. They revealed that there is no major objection and that clarification regarding the treatment instituted proved to be important in the acceptance decision. Conclusion: the feelings expressed by the patients, such as improvement of the wound, reduction of pain and odor, optimization of the healing process, emergence of sparks of hope regarding the return to their life, among others, translate the benefits of Larval Therapy (LT). Despite the seizure caused by the animal’s movement over the affected area and the disgust it causes to some professionals and people, LT was considered wonderful, especially for its effectiveness in cleaning the wound without the need for new invasive procedures such as cutting and surgical debridement.